MARKETING STRATEGY TO INCREASE MARKET SHARE OF PT ANINDYA WIRAPUTRA KONSULT'S IN THE VPTI (IMPORT TECHNICAL VERIFICATION) AMIDST COMPETITION WITH STATE-OWNED ENTERPRISES - Aryadhani, Sinatrya Azali; Mustika Sufiati Purwanegara (CV. Radja Publika, 2025)
This research investigates the strategic positioning of PT Anindya Wiraputra Konsult (Anindya), a private surveying firm, within Indonesia's iron and steel Verification of the Implementation of Import Techniques (VPTI) market. Despite substantial import volumes and mandatory VPTI, Anindya captured only a 20.28% market share in 2019, lagging behind the dominant state-owned enterprise, KSO SCISI. This study critically evaluates Anindya's brand perception against its main competitor, identifies key factors driving client selection of VPTI providers, and assesses the market impact of Anindya’s strategic initiatives focused on expertise, agility, technology, and partnerships. Employing a mixed-methods research design, the study combines an internal analysis of Anindya, leveraging company documents and management insights through the Resource-Based View, with a comprehensive external analysis encompassing PESTEL, a market overview, and a consolidated SWOT analysis. The empirical foundation is a market survey of 50 client companies (importers, manufacturers, traders) in the Indonesian iron and steel sector. This survey yielded quantitative and qualitative data on comparative brand perceptions, decision-making hierarchies, and the perceived effectiveness of Anindya's strategic emphases. Analytical frameworks include Segmentation, Targeting, and Positioning (STP), B2B decision-making theories, and brand trust concepts, informing a robust analysis.